Síntese da perovskita KBiFe2O5 (KBFO), via diferentes rotas, com potencial aplicação em células solares - Verza, Jhonata Rafael (Universidade Federal de São Carlos, 2020)
Clean energies have become a growing quest for sustainable development. Within this context, solar energy stands out, which is renewable, practically inexhaustible and clean. The solar cell is the main instrument that converts solar energy into electric energy, and the active layer is the heart of this device, it is in it that the converter material is found that is responsible for this process. Among these materials, perovskites have been attracting the attention of research due to its versatility in applications, so that perovskite KBiFe2O5 showed a great application potential due to its band gap close to ideal for photovoltaic applications, that value is approximately 1.4 eV. Therefore, seeking synthesis methods that align simplicity and formation of a single-phase system is of great interest, since secondary phases can generate the recombination of load-bearing pairs generated and decrease conversion efficiency. Thus, the present work aimed at the synthesis of this perovskite via different routes, evaluating the best route for the formation of a single-phase system and evaluating its potential application through band gap analysis. For this, the methods of combustion in solution, polymeric precursors and hydrothermal were used, in view of the results, the three synthesis methods used were efficient for the formation of perovskite, and the polymeric precursor method proved to be the most effective for the production of a single-phase system. Due to an average band gap value of 1.7 eV obtained, it is understood that this perovskite is promising for photovoltaic applications and can be produced in a simple way and adapted to produce thin films.
Synthesis of perovskite KBiFe2O5 (KBFO) by different routes with potencial application in solar cells
Keywords: Combustão; Pechini; Hidrotermal; Energia solar; Band gap; Combustion; Hydrothermal; Solar energy; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::CERAMICOS